2021
DOI: 10.1016/j.jfineco.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Creditor control rights and resource allocation within firms

Abstract: The research program of the Center for Economic Studies (CES) produces a wide range of economic analyses to improve the statistical programs of the U.S. Census Bureau. Many of these analyses take the form of CES research papers. The papers have not undergone the review accorded Census Bureau publications and no endorsement should be inferred. Any opinions and conclusions expressed herein are those of the author(s) and do not necessarily represent the views of the U.S. Census Bureau. All results have been revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 98 publications
0
30
0
Order By: Relevance
“…Among the reasons for the divergent conclusions of existing research is that of the tendency to overlook the role of executives in corporate innovation activities (Shao et al, 2020). As the main decision-making body, who are also responsible for the execution and supervision of innovation activities, enterprise executives' decisions and willingness with respect to innovation directly affect the allocation efficiency of innovation resources, which in turn impacts the extent to which enterprises engage in technological innovation (Hao et al, 2019;Sarfraz et al, 2020;Ersahin et al, 2021;Zhao et al, 2021;Zhou et al, 2021). Research based on principal-agent theory has demonstrated that, as a result of the high uncertainty and lengthy return cycles associated with innovation activities, executives choose less innovation investment based on self-interest, resulting in diminished resource allocation efficiency (Huang et al, 2014;Si et al, 2020;Zheng et al, 2020;Jin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Among the reasons for the divergent conclusions of existing research is that of the tendency to overlook the role of executives in corporate innovation activities (Shao et al, 2020). As the main decision-making body, who are also responsible for the execution and supervision of innovation activities, enterprise executives' decisions and willingness with respect to innovation directly affect the allocation efficiency of innovation resources, which in turn impacts the extent to which enterprises engage in technological innovation (Hao et al, 2019;Sarfraz et al, 2020;Ersahin et al, 2021;Zhao et al, 2021;Zhou et al, 2021). Research based on principal-agent theory has demonstrated that, as a result of the high uncertainty and lengthy return cycles associated with innovation activities, executives choose less innovation investment based on self-interest, resulting in diminished resource allocation efficiency (Huang et al, 2014;Si et al, 2020;Zheng et al, 2020;Jin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher corporate loans encourage creditors to increase oversight of management in making tax policies so as not to endanger creditors. On the other hand (Ersahin et al, 2021) also found that creditor intervention had an effect on increasing firm value. Therefore, creditors have a strong role in corporate tax policymaking.…”
Section: H1b: Tunnelling Incentive Affects Corporate Tax Policymentioning
confidence: 94%
“…The higher the company's debt ratio, the company manager will choose accounting methods that can increase a company's profit (Junaidi and Zs, 2020). Creditors, like owners, also have the power to influence management in policy making because the capital used in running a business is the result of creditor negotiations, so there are things that management is finally forced to consider over the control of these creditors (Ersahin et al, 2021). Even so, the influence of debt covenants does not always have an influence on the company's decision to do transfer pricing (Mintorogo and Djaddang, 2019;Sujana et al, 2022).…”
mentioning
confidence: 99%
“…However, due to the sheer volume of funds granted as credit to firms vis-à-vis with equity funding, creditors are an important source of corporate financing, especially as the main source of fresh capital (Jandik and McCumber, 2018;Robb and Robinson, 2014). Moreover, there exists an alternative view that rejects the passive nature of creditors' governance, which provides ample evidence indicating the effectiveness of creditors not restricted to the governance of bankrupt firms alone but also under the circumstances of technical default (Bharath and Hertzel, 2019;Ersahin et al, 2021;Nini et al, 2012) [1].…”
Section: Introductionmentioning
confidence: 99%